HUBUNGAN INTENSITAS PENGGUNAAN GADGET DENGAN PRESTASI BEAJAR ANAK USIA SEKOLAH DI SD KARTIKA X-5 KALIDERES JAKARTA BARAT - nur, nurkhasanah789; Rochmani, Siti (Nusantara Hasana Journal, 2022)
Gadget usage is not only used by adults or the elderly.but also by adolescents.advanced adults even children age 3-6 years who as difficult as do not have a gadget if elementary school children use gadgets to add knowledge can have an impact on student achievement in school. Purpose: To determine the relationship between the use of gadgets and the learning achievement of school age children,to determine the intensity of gadget use at school age children,the intensity of gadget use and learning achievement. Method: This research is a quantitative research, with a descriptive correlation design. Sample taken by random sampling technique with a cross sectional approach. Results: From the results of the bivariate analysis using the chi square test, the p-value is 0.318 (â‰¥0.05), so it can be concluded that there is no relationship between the intensity of gadget use and learning achievement in school-age children at SD Kartika X-5 Conclusion: The results of respondents who were female were 115 female and 39 were male. The results of the respondents using high intensity were 9.7%, moderate intensity was 27.3%, and low intensity was 63%.Â